Organize & create discipline : an A-to-Z guide to an organized existence - Klosky, Justin (Avery, 2013)
" A professional organizer's complete guide to getting-and staying-organized. As a child, Justin Klosky loved to count, analyze, and categorize everything in sight. Eventually diagnosed with OCD, he found ways to tap the benefits of his condition. Today, he's founded a successful firm, O.C.D. Experience, building on the principals of Organize, Create, Discipline to help high-end clients take control of their lives through time management skills, getting rid of clutter, simplifying their habits, and rethinking storage solutions. Carefully arranged into more than 300 A-to-Z categories, Organize & Create Discipline explains organization methods for everything from laundry to legal documents, shoes, toys, kitchen drawers, medicine cabinets, utility closets, overflowing email inboxes, and dozens of other sources of daily detritus. Klosky's unique advice yields peace of mind and radically improves productivity. With a clientele that includes Bryce Dallas Howard, Julie Chen, and Saks Fifth Avenue, Klosky now makes his unrivaled techniques to staying organized available to all"--